Ni(II), Cu(II), Mn(II), and Fe(II) Metal Complexes Containing 1,3-Bis(diphenylphosphino)propane and Pyridine Derivative: Synthesis, Characterization, and Antimicrobial Activity - Maged S. Al-Fakeh; Gadah A. Allazzam; Naeema H. Yarkandi (International Journal of Biomaterials)
Four of the coordination compounds of the general formula, [M(DPPP)(APY)(H2O) Cl2].xH2O, where M = Ni(II), Cu(II), Mn(II), and Fe(II) and x = 0, 1, or 2 molecules of H2O, DPPP = 1,3-bis(diphenylphosphino)propane, and APY = 2-aminopyridine, have been prepared and characterized. The structure of the complexes has been confirmed by elemental analysis, FT-IR, and UV-Vis spectral data. Thermal analysis (thermogravimetry, derivative thermogravimetry, and differential thermal studies) has been used to study the thermal decomposition stages. Biological activity of all synthesized complexes was tested against five bacterial strains and three fungal strains. Bacteria and fungi strains are common contaminants of the environment in Saudi Arabia, some of which are frequently reported from contaminated water, soil, and food.